After Mexico : emerging markets, emerging crises?. - KLEIN, Lawrence R. (1996)
Argues that political factors contributed significantly to the Mexican crisis, and notes that there are more such crises on the horizon. Offers three types of proposals to deal with future crises of a similar nature, viz. (1) better and more timely information along with an earlier response to it by the IMF; (2) a 'syndicate-agent' role and an auditing responsibility for the IMF; and (3) a 'bankrupt-court' function for the IMF when a country is deemed insolvent.